A Luminescent Nitrogen‐Containing Polycyclic Aromatic Hydrocarbon Synthesized by Photocyclodehydrogenation with Unprecedented Regioselectivity. Issue 49 (22nd October 2015) - Gu, Xinggui; Wang, Hong; Roose, Jesse; He, Zikai; Zhou, Yue; Yan, Yongli; Cai, Yuanjing; Shi, Heping; Zhang, Yilin; Sung, Herman H. Y.; Lam, Jacky W. Y.; Miao, Qian; et al.
Abstract: We present a nitrogen‐containing polycyclic aromatic hydrocarbon (N‐PAH), namely 12‐methoxy‐9‐(4‐methoxyphenyl)‐5, 8‐diphenyl‐4‐(pyridin‐4‐yl)pyreno[1, 10, 9‐ h, i, j ]isoquinoline ( c ‐TPE‐ON), which exhibits high quantum‐yield emission both in solution (blue) and in the solid state (yellow). This molecule was unexpectedly obtained by a three‐fold, highly regioselective photocyclodehydrogenation of a tetraphenylethylene‐derived AIEgen. Based on manifold approaches involving UV/Vis, photoluminescence, and NMR spectroscopy as well as HRMS, we propose a reasonable mechanism for the formation of the disk‐like N‐PAH that is supported by density functional theory calculations. In contrast to most PAHs that are commonly used, our system does not suffer from entire fluorescence quenching in the solid state due to the peripheral aromatic rings preventing π–π stacking interactions, as evidenced by single‐crystal X‐ray analysis. Moreover, its rod‐like microcrystals exhibit excellent optical waveguide properties. Hence, c ‐TPE‐ON comprises a N‐PAH with unprecedented luminescent properties and as such is a promising candidate for fabricating organic optoelectronic devices. Our design and synthetic strategy might lead to a more general approach to the preparation of solution‐ and solid‐state luminescent PAHs. Abstract : Unprecedented luminescence : A luminescent nitrogen‐containing polycyclic aromatic hydrocarbon (N‐PAH) has been synthesized from a vinylene‐based AIEgen by a photocyclodehydrogenation reaction with unexpected regioselectivity. The N‐PAH exhibits excellent optical properties both in solution and in the solid state (see figure).